A plateau of potatoes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Potatoes are hot stuff on the plateau of Fouta Djalon in Guinée. In the last ten years, productivity has risen more than four-fold (up to 22 tonnes/ hectare from 5 t/ha). More than 2,000 tonnes are sold annually on the local markets, but also to...